The Role of Religious Aspects on Life Satisfaction: Case Study of Muslims in Indonesia - Kiky Nur Fauzi (Universitas Muhammadiyah Yogyakarta, 2022)
Religiosity aspect is the most important part in personal life. With religion, an individual can achieve true peace, including life satisfaction. Life satisfaction is actually one of the most important aspects of a goal in life. This study aims to determine the role of religiosity and economic aspect on the level of one's life satisfaction. Life satisfaction was measured using a life satisfaction scale, while religiosity was measured using subjective perceptions of religiosity, frequency of prayer, frequency of attending recitations, and affiliation to religious organizations. This study was limited to a sample of Muslims aged 15 to 64 years in the fifth round of the 2014 Indonesia Family Life Survey (IFLS) database. Using ordered logit regression, statistical evidence was obtained that the aspect of religiosity was positively related to life satisfaction. Each increase in one level of religiosity was associated with 8.1% increase in the probability of being satisfied. This finding is supported by variables that reflect other aspects of religiosity, such as an increase in one level of prayer frequency associated with an increase in the probability of being satisfied by 1.4%. Meanwhile, the economic aspects as measured by education level and work status are positively associated with life satisfaction.